Functional Materials For Energy, Sustainable Development and Biomedical Sciences - Wegner, Gerhard; Wegner, Gerhard; Allard, Nicolas; Allard, Nicolas; Al Shboul, Ahmad; Al Shboul, Ahmad; Auger, Michèle; Auger, Michèle; Beaulieu, Ann-Marie; Beaulieu, Ann-Marie; Bélanger, Daniel; Bélanger, Daniel; et al. (De Gruyter, 2014)
Functional organic materials are increasingly important in cutting-edge applications such as energy production, storage and conversion, biomedicine and sustainable development. Top-notch specialists have created a unique and timely overview for undergraduate (final year) and graduate students with a background in chemistry but should also be useful for physicists and engineers.- Resumé vydavatel
Lizenzpflichtig
Keywords: inteligentní materiály; smart materials; elektronické knihy; učebnice; electronic books; textbooks